Diagnosis Profile and PTSD Comorbidity of Syrian Refugees Sample from Refugee Mental Health Branch Polyclinic - Ersin Uygun (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi, 2019)
Aim: It was aimed to evaluate the Syrians who applied to a special adult refugee mental health outpatient clinic in Istanbul for a year and to asses them for psychiatric disorders and comorbidity. Method: The Structured Clinical Interview for the DSM-IV Axis I Disorders (SCID-I) was applied in Arabic language to the Syrian volunteers who applied to the Bakirkoy Mental Health and Diseases Training and Research Hospital (BRHSS) refugee mental health policlinic to get mental health service during 2017. Results: 107 participants included in the study and seven (6.5%) of them were not diagnosed in any disorder according to the DSM criteria. The most frequent diagnoses were major depression (56.1%), posttraumatic stress disorder (38.4%), bipolar disorder (10.2%) and psychotic disorder (7.5%). Only 7 (17%) of the 41 patients diagnosed with posttraumatic stress disorder had no other psychiatric disorder in addition to PTSD. At the same time, psychiatric co-morbidity for PTSD was 70% for major depression, 7.5% for bipolar disorder and 2.4% for dissociative disorder. Conclusion: in the direction of our findings, while we are assesing a Syrian patient who has a traumatic stress symptoms, its highly possible to find another psychiatric disorder as co-morbid like depression and bipolar disorder. Morover we should use an inclusive model which includes both experienced trauma and experienced losses while taking the history and planning the treatment. [JCBPR 2019; 8(1.000): 51-57]